EXPERIENCE OF UZBEKISTAN AND EDUCATION OF PEDAGOGICAL RESPONSIVENESS AMONG FUTURE DEFECTOLOGISTS - Nodira Mirbabayeva (Journals Park Publishing, 2024)
The main idea of the article is devoted to the comparison and analysis of the experience of Uzbekistan and abroad in the formation of pedagogical responsibility among future defectologists. Important ways of developing the pedagogical responsibility of Future defectologists are discussed, including practical training, independent study and Research activities.
Keywords: educational process, pedagogical responsiveness, interest, foreign experience, defectologist, experience, professional activity.